Estimating the global prevalence of secondary hyperparathyroidism in patients with chronic kidney disease - Wang, Yichao; Liu, Jiaye; Fang, Yiqiao; Zhou, Shengliang; Liu, Xueting; Li, Zhihui (Frontiers in Endocrinology, 2024)
Background: Chronic kidney disease (CKD)-related secondary hyperparathyroidism (SHPT) is associated with higher morbidity and death. This study's goal was to mine the SHPT data already available to do a meta-analysis on the global prevalence of SHPT 2 caused by CKD. Methods: Embase, Medline, Web of Science, Cochrane Central Databases, and Google Scholar were searched to identify studies on the prevalence of SHPT due to CKD from inception to November 2023. Pooled prevalence was calculated by using the DerSimonian-Laird random effects model with Logit transformation.Results: Twenty-one eligible studies involving 110977 patients were included. Our results revealed that the estimated global prevalence of SHPT due to CKD was 49.5% (95% CI 30.20-68.18) regardless of the diagnostic criteria. For subgroup analysis, Southern Asia (84.36%, 95% CI 79.35-88.34) had a significantly higher SHPT prevalence than other geographic regions. SHPT due to CKD was most prevalent in China (85.14%, 95% CI 81.74-88.00).SHPT due to CKD is highly prevalent. This necessitates awareness and therapeutic approach from primary care physicians, medical professionals, health strategies authorities.